Principles of Neutron Scattering from Condensed Matter. By Andrew T. Boothroyd. Oxford University Press, 2020. Pp. 512. Price GBP 55.00. ISBN 9780198862314. Issue 2 (19th February 2021) - Proffen, Thomas
Abstract : Book review Abstract : Book review